PENGARUH EMPLOYEE ENGAGEMENT DAN WORKLIFE BALANCE TERHADAP TURNOVER INTENTION DENGAN DIMEDIASI KEPUASAN KERJA - Durrotun Nafisah, Bella Mutia; Husainah, Nazifah (Taksasila Edukasi Insani, 2025)
The purpose of this study is to determine the effect of employee engagement and work-life balance on job satisfaction and its implications on turnover intention among Generation Z employees in South Tangerang City. This study is a quantitative, associative study using primary data. The sample consisted of 230 Generation Z employees in South Tangerang City. Data were collected by distributing 230 questionnaires directly to respondents via Google Forms. The analysis method used was Structural Equation Model – Partial Least Square (SEM-PLS). The results showed that employee engagement and work-life balance had a positive and significant effect on employee job satisfaction. Meanwhile, employee engagement, work-life balance, and job satisfaction had a negative and significant effect on employee turnover intention. Additionally, job satisfaction mediates the influence of employee engagement and work-life balance on turnover intention among Generation Z employees in South Tangerang City.Keywords : employee engagement, job satisfaction, turnover intention, work-life balance